2024
DOI: 10.2174/0929867331666230727103553
|View full text |Cite
|
Sign up to set email alerts
|

Aducanumab in Alzheimer’s Disease: A Critical Update

Abstract: Alzheimer's disease (AD) is a complex neurological disorder that results in cognitive decline. The incidence rates of AD have been increasing, particularly among individuals 60 years of age or older. In June 2021, the US FDA approved aducanumab, the first humanized monoclonal antibody, as a potential therapeutic option for AD. Clinical trials have shown this drug to effectively target the accumulation of Aβ (beta-amyloid) plaques in the brain, and its effectiveness is dependent on the dosage and duration of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Nonetheless, research has demonstrated that the modulation of cytokines can offer a means to manage neuroinflammation, thereby unveiling novel therapeutic avenues. 23,27,28 The intricate interplay between viral infections and the immune system has been a longstanding subject of scientific investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, research has demonstrated that the modulation of cytokines can offer a means to manage neuroinflammation, thereby unveiling novel therapeutic avenues. 23,27,28 The intricate interplay between viral infections and the immune system has been a longstanding subject of scientific investigation.…”
Section: Introductionmentioning
confidence: 99%